A plea for pantheism - Hittell, John S. 1825-1901; Library of Congress (New York C. Blanchard, 1857)
Preface.--Physiology vs. a future state.--Pantheism vs. anthropomorphism.--Moral responsibility.--Absolute turth unattainable by man.
Keywords: Pantheism; Religion